Analisis Penerimaan dan Penggunaan Teknologi Ojek Online dengan TAM - Hanna Christina; Usep Suhud; Mohamad Rizan (Faculty of Economics, State University of Jakarta., 2018)
The purpose of this research is to examine factors acceptance and use behaviour of motorcycle online. A conceptual framework has been developed based on the Technology Acceptance Model (TAM) theory. A questionnaire was developed and used to collect information from 358 respondents from motorcycle online user.Questionnaire survey was conducted in South Tangerang, Indonesia. The quantitative research methode was used with convenience method of sampling. The results reveal that the Perceived Ease of Use also has influence to Perceived Usefulness and Perceived Usefulness has significant influence to behavioural intention. Attitudes also positively influencing the behavioural intention motorcycle online. Facilitating Condition have significant influence to use behaviour of the motorcycle online. Behaviour intention has a positive impact on use behaviour of the motorcycle online. Keywords: Technology Acceptance Model, Penerimaan Dan Penggunaan Teknologi Ojek Online, UTAUT,Perilaku Konsumen.